Analisis Kemandirian Keuangan Daerah Kabupaten Flores Timur - Konstantinus Pati Sanga; Wihelmina Maryetha Yulia Jaeng (Departement of Mathematics Education, 2023)
This study aims to analyze the financial independence of the East Flores Regency area. The type of research used is quantitative descriptive research. This study used secondary data, namely data obtained from the Financial Audit Agency (BPK) of the Republic of Indonesia. The secondary data in this case is the East Flores District Local Government Budget Realization Report from 2016-2020.The analysis used in this study is related to the analysis of financial ratios using the Regional Financial Independence Ratio. The results of the analysis show that the financial independence of the East Flores Regency area is very low with a pattern of instructive relationships. This means that the East Flores Regency Government receives more direction and guidance from the central government so that the role of the central government is more dominant than the financial independence of the local government itself.